A high-efficiency liquid desulfurization and slag removal agent and its preparation method

By using functionalized rare earth nanomaterials and limestone powder in liquid desulfurization and methyl acrylate to form a dendritic structure in liquid desulfurization and slag removal agent, the low desulfurization efficiency and insufficient sulfur solidification rate in the existing desulfurization process are solved. The problem has achieved efficient and stable boiler desulfurization and slag removal effect.

CN118807440BActive Publication Date: 2024-12-27HEJIAN HUASHUN CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411302780.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-27
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

The existing desulfurization process has problems such as low desulfurization efficiency, insufficient sulfur solidification rate, complex use and easy blockage. In particular, the liquid desulfurization agent is low in efficiency during the stirring and dissolution process and can easily lead to blockage of the nozzle, and the existing calcium-based sulfur solidification agent is in the boiler. Internal decomposition affects combustion efficiency.

Method used

A high-efficiency liquid desulfurization and slag removal agent is used, and its raw materials include limestone powder, catalyst, oleic acid, sodium hydroxide, yttrium chloride, sodium fluoride, sodium dichromate, ethylenediamine, methyl acrylate and sodium tripolyphosphate , the rare earth nanomaterials and limestone powder are functionalized by hydrothermal method, and the dendritic structure is formed by combining ethylenediamine and methyl acrylate to form a dendritic structure, enhancing the stability and dissolution rate of the desulfurization and residue removal agent to avoid agglomeration.

Benefits of technology

Improve the boiler combustion efficiency, extend the garbage combustion time, significantly improve the desulfurization and slag removal rate, reduce energy consumption and cost, ensure stable operation of the equipment, the desulfurization and slag removal rate reaches more than 95%, and maintain 92% under high temperature conditions. The above efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to the technical field of liquid desulfurization slag remover, and specifically discloses a high-efficiency liquid desulfurization slag remover, wherein the raw materials include by mass: 5-15 parts of limestone powder, 0.1-1 parts of catalyst, 20-25 parts of oleic acid, 1-3 parts of sodium hydroxide, 0.1-1 parts of yttrium chloride, 0.0403-0.1550 parts of sodium fluoride, 0.0131-0.3830 parts of sodium dichromate, 1-3 parts of ethylenediamine, 2-5 parts of methyl acrylate, 5-15 parts of sodium tripolyphosphate, and 20-35 parts of sodium chlorite. The present invention also discloses a preparation method of the above-mentioned high-efficiency liquid desulfurization slag remover. The present invention has no odor, no irritating smell, and no polluting components to the body and the environment; it is not easy to block the nozzle, and it can not only effectively remove the slag body in the softened dust in the smoke, prevent coking, effectively reduce energy consumption and cost, and significantly improve the efficiency of the entire desulfurization system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of liquid desulfurization and deslagging agents, and in particular to a high-efficiency liquid desulfurization and deslagging agent and a preparation method thereof. Background Art

[0002] Incineration power generation has become the main way to treat urban domestic waste in my country. Urban domestic waste generally contains sulfur, which is thermally decomposed and oxidized during the combustion process to produce small molecular gases mainly composed of SO2. However, SO2 is an irritating and highly toxic gas. When released into the atmosphere, it can generate sulfuric acid and sulfate-containing aerosols through photochemical reactions, leading to acid rain and haze. The garbage combustion process in the incineration boiler generally has two thermodynamic directions: decarbonization cracking reaction and dehydrogenation condensation reaction. The former is manifested as combustion, and the latter is mainly manifested as ash and coking.

[0003] The existing desulfurization processes mainly include: ammonia flue gas desulfurization and double alkali flue gas desulfurization. Among them, ammonia flue gas desulfurization has high desulfurization efficiency and fast reaction rate, but the absorbent cost is high; the double alkali flue gas desulfurization system is simple and not easy to scale or clog, but the process is complicated and not mature.

[0004] At present, calcium-based desulfurizers, which are mainly limestone, absorb heat when heated and decomposed in the furnace, which affects the combustion thermal efficiency of the boiler to varying degrees, and the desulfurization rate is only 40-60%, which limits their use. Although liquid desulfurizers can increase the desulfurization rate, they need to be stirred and dissolved before use, which is not only complicated and affects efficiency, but also prone to nozzle clogging; at the same time, the desulfurization and slag removal efficiency is low, the effect is poor, and frequent furnace shutdowns and cleaning are required. Summary of the invention

[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a high-efficiency liquid desulfurization and deslagging agent and a preparation method thereof.

[0006] A high-efficiency liquid desulfurization and slag removal agent, whose raw materials include, by mass, 5-15 parts of limestone powder, 0.1-1 parts of catalyst, 20-25 parts of oleic acid, 1-3 parts of sodium hydroxide, 0.1-1 parts of yttrium chloride, 0.0403-0.1550 parts of sodium fluoride, 0.0131-0.3830 parts of sodium dichromate, 1-3 parts of ethylenediamine, 2-5 parts of methyl acrylate, 5-15 parts of sodium tripolyphosphate and 20-35 parts of sodium chlorite.

[0007] Preferably, the catalyst is sodium chlorate.

[0008] Preferably, the limestone powder is obtained by crushing, grinding and screening limestone.

[0009] More preferably, the screen is 100-200 mesh.

[0010] The preparation method of the above-mentioned high-efficiency liquid desulfurization and deslagging agent comprises the following steps:

[0011] S1. Add ethanol aqueous solution to oleic acid and stir evenly, add sodium hydroxide and stir evenly, add yttrium chloride and stir for 5-15 minutes, add sodium fluoride aqueous solution and continue stirring for 1-5 minutes, perform hydrothermal treatment at 180-200° C. for 5-10 hours, add cyclohexane to precipitate after cooling, and wash to obtain activated rare earth;

[0012] S2, adding activated rare earth to water, adding sodium dichromate aqueous solution thereto under stirring, continuing stirring for 10-30 hours, centrifuging, washing, vacuum drying, adding to water and stirring evenly, adding limestone powder thereto and stirring for 1-2 hours, adding a catalyst and stirring to obtain a premix;

[0013] S3. Add ethylenediamine to methanol and stir evenly, add methyl acrylate, stir at 40-50°C for 10-20h under nitrogen protection, heat to 70-80°C and distill under reduced pressure, stir at 120-130°C for 1-2h, cool to room temperature, add to the premix and stir evenly, add sodium tripolyphosphate, stir at 60-70°C for 10-20min, add sodium chlorite, stir for 1-3h, and cool to room temperature.

[0014] Preferably, in S1, the mass fraction of the ethanol aqueous solution is 30-50%.

[0015] Preferably, in S1, the concentration of the sodium fluoride aqueous solution is 1-2 mol / L.

[0016] Preferably, in S1, the hydrothermal treatment temperature is 185-195° C., and the hydrothermal treatment time is 7-9 h.

[0017] Preferably, in S2, the concentration of the sodium dichromate aqueous solution is 0.01-0.1 mol / L. Beneficial Effects

[0018] 1. The present invention uses a hydrothermal method to functionalize oleic acid on the surface of rare earth nanomaterials, and then promotes double bond oxidation through strong oxidation with sodium dichromate, thereby making the rare earth nanomaterials have good water solubility, which can be compounded with limestone powder to quickly disperse and penetrate into the gaps of incinerated garbage, and can also cooperate with sodium chlorate for catalysis, and can continuously activate oxygen molecules at a relatively low temperature to generate sufficient oxygen free radicals for oxidation reaction.

[0019] The present invention reduces the ignition point of garbage, prolongs the burning time of garbage, increases the burning intensity, strips off old flue dust, inhibits and slows down the generation of new dust, thereby improving the efficiency of the boiler to achieve the purpose of cleaning.

[0020] 2. The present invention combines ethylenediamine with methyl acrylate to form a dendritic structure, the surface of which contains a large number of anchoring groups. The material is dispersed through steric hindrance effect and electrostatic repulsion, effectively preventing agglomeration and quickly eliminating the generation of coke slag. At the same time, it has good compatibility with rare earth nanomaterials. On the one hand, it can effectively enhance the stability of the desulfurization and slag removal agent on the basis of reducing the viscosity of the system. On the other hand, it can significantly enhance the dissolution rate of sulfur-containing gas and the mass transfer rate in the system. Under the synergistic effect, it not only has a strong temperature adaptability, but also has a significant desulfurization efficiency and slows down the generation of agglomeration.

[0021] 3. The nozzle is not easily clogged in the present invention. The present invention can not only effectively remove the slag in the softened dust in the smoke and prevent coking, but also effectively reduce energy consumption and cost, and significantly improve the efficiency of the entire desulfurization system. The concentration of 20-50ppm can ensure the stable operation of the equipment, and the desulfurization and slag removal rate is as high as more than 95%. Moreover, the temperature adaptability is strong. Under the temperature condition of 300°C, the desulfurization and slag removal rate is still maintained at more than 92%.

[0022] 4. The invention has no peculiar smell, no irritating smell, and no polluting components to the human body and the environment. DETAILED DESCRIPTION

[0023] The present invention will be further explained below in conjunction with specific embodiments. Example 1

[0024] A high-efficiency liquid desulfurization and slag removal agent, whose raw materials include: 5kg of 100-mesh limestone powder, 0.1kg of sodium chlorate, 20kg of oleic acid, 1kg of sodium hydroxide, 0.1kg of yttrium chloride, 0.0403kg of sodium fluoride, 0.0131kg of sodium dichromate, 1kg of ethylenediamine, 2kg of methyl acrylate, 5kg of sodium tripolyphosphate, and 20kg of sodium chlorite.

[0025] The preparation method of the above-mentioned high-efficiency liquid desulfurization and deslagging agent comprises the following steps:

[0026] S1. Add 5 kg of 30% ethanol aqueous solution to oleic acid and stir evenly, add sodium hydroxide and stir evenly, add yttrium chloride thereto, stir at a speed of 500 r / min for 5 min, add 1 mol / L sodium fluoride aqueous solution thereto, continue stirring for 1 min, send into a hydrothermal reactor, treat at a temperature of 180°C for 5 h, add cyclohexane to precipitate after cooling, wash with ethanol to obtain activated rare earth;

[0027] S2, adding activated rare earth to 20kg water, adding thereto a sodium dichromate aqueous solution with a concentration of 0.01mol / L under stirring, stirring at a speed of 500r / min for 10h, centrifuging, washing, vacuum drying, adding to 30kg water and stirring evenly, adding limestone powder thereto and stirring for 1h, stirring speed of 50r / min, adding sodium chlorate and stirring for 1h to obtain a premix;

[0028] S3. Add ethylenediamine to 10 kg of methanol and stir evenly. Add methyl acrylate, stir at 40°C for 10 hours under nitrogen protection, heat to 70°C and distill under reduced pressure, stir at 120°C for 1 hour, cool to room temperature, add to the premix and stir evenly, add sodium tripolyphosphate, stir at 60°C for 10 minutes, add sodium chlorite, stir for 1 hour, and cool to room temperature. Example 2

[0029] A high-efficiency liquid desulfurization and slag removal agent, whose raw materials include: 15kg of 200-mesh limestone powder, 1kg of sodium chlorate, 25kg of oleic acid, 3kg of sodium hydroxide, 1kg of yttrium chloride, 0.1550kg of sodium fluoride, 0.3830kg of sodium dichromate, 3kg of ethylenediamine, 5kg of methyl acrylate, 15kg of sodium tripolyphosphate, and 35kg of sodium chlorite.

[0030] The preparation method of the above-mentioned high-efficiency liquid desulfurization and deslagging agent comprises the following steps:

[0031] S1. Add 15 kg of 50% ethanol aqueous solution to oleic acid and stir evenly, add sodium hydroxide and stir evenly, add yttrium chloride thereto, stir at a speed of 1000 r / min for 15 min, add 2 mol / L sodium fluoride aqueous solution thereto, continue stirring for 5 min, send into a hydrothermal reactor, treat at a temperature of 200 ° C for 10 h, add cyclohexane to precipitate after cooling, wash with ethanol to obtain activated rare earth;

[0032] S2, activated rare earth is added to 40kg water, and a sodium dichromate aqueous solution with a concentration of 0.1mol / L is added thereto under stirring, stirred for 30h at a speed of 1000r / min, centrifuged, washed, vacuum dried, added to 60kg water and stirred evenly, limestone powder is added thereto and stirred for 2h, the stirring speed is 120r / min, sodium chlorate is added and stirred for 2h, and a premix is ​​obtained;

[0033] S3. Add ethylenediamine to 15 kg of methanol and stir evenly. Add methyl acrylate, stir at 50°C for 20 hours under nitrogen protection, heat to 80°C and distill under reduced pressure, stir at 130°C for 2 hours, cool to room temperature, add to the premix and stir evenly, add sodium tripolyphosphate, stir at 70°C for 20 minutes, add sodium chlorite, stir for 3 hours, and cool to room temperature. Example 3

[0034] A high-efficiency liquid desulfurization and slag removal agent, whose raw materials include: 8kg of 150-mesh limestone powder, 0.7kg of sodium chlorate, 21kg of oleic acid, 2.5kg of sodium hydroxide, 0.2kg of yttrium chloride, 0.1203kg of sodium fluoride, 0.1235kg of sodium dichromate, 2.5kg of ethylenediamine, 3kg of methyl acrylate, 12kg of sodium tripolyphosphate, and 25kg of sodium chlorite.

[0035] The preparation method of the above-mentioned high-efficiency liquid desulfurization and deslagging agent comprises the following steps:

[0036] S1. Add 12 kg of 35% ethanol aqueous solution to oleic acid and stir evenly, add sodium hydroxide and stir evenly, add yttrium chloride thereto, stir at a speed of 900 r / min for 8 min, add 1.8 mol / L sodium fluoride aqueous solution thereto, continue stirring for 2 min, send into a hydrothermal reactor, treat at a temperature of 195°C for 7 h, add cyclohexane to precipitate after cooling, wash with ethanol to obtain activated rare earth;

[0037] S2, activated rare earth is added to 35kg water, and a sodium dichromate aqueous solution with a concentration of 0.03mol / L is added thereto under stirring, stirred for 15h at a speed of 900r / min, centrifuged, washed, vacuum dried, added to 50kg water and stirred evenly, limestone powder is added thereto and stirred for 80min, the stirring speed is 100r / min, sodium chlorate is added and stirred for 80min, and a premix is ​​obtained;

[0038] S3. Add ethylenediamine to 14 kg of methanol and stir evenly. Add methyl acrylate, stir at 42 °C for 18 h under nitrogen protection, heat to 73 °C and distill under reduced pressure, stir at 128 °C for 80 min, cool to room temperature, add to the premix and stir evenly, add sodium tripolyphosphate, stir at 68 °C for 12 min, add sodium chlorite, stir for 2.5 h, and cool to room temperature. Example 4

[0039] A high-efficiency liquid desulfurization and slag removal agent, whose raw materials include: 12kg of 150-mesh limestone powder, 0.3kg of sodium chlorate, 23kg of oleic acid, 1.5kg of sodium hydroxide, 0.8kg of yttrium chloride, 0.0792kg of sodium fluoride, 0.3071kg of sodium dichromate, 1.5kg of ethylenediamine, 4kg of methyl acrylate, 8kg of sodium tripolyphosphate, and 30kg of sodium chlorite.

[0040] The preparation method of the above-mentioned high-efficiency liquid desulfurization and deslagging agent comprises the following steps:

[0041] S1. Add 8 kg of 45% ethanol aqueous solution to oleic acid and stir evenly, add sodium hydroxide and stir evenly, add yttrium chloride thereto, stir at a speed of 700 r / min for 12 min, add 1.2 mol / L sodium fluoride aqueous solution thereto, continue stirring for 4 min, send into a hydrothermal reactor, treat at a temperature of 185°C for 9 h, add cyclohexane to precipitate after cooling, wash with ethanol to obtain activated rare earth;

[0042] S2, activated rare earth is added to 25kg water, and a sodium dichromate aqueous solution with a concentration of 0.07mol / L is added thereto under stirring, stirred for 25h at a speed of 700r / min, centrifuged, washed, vacuum dried, added to 40kg water and stirred, limestone powder is added thereto and stirred for 100min, the stirring speed is 60r / min, sodium chlorate is added and stirred for 100min, and a premix is ​​obtained;

[0043] S3. Add ethylenediamine to 12 kg of methanol and stir evenly. Add methyl acrylate, stir at 48 °C for 12 h under nitrogen protection, heat to 77 °C and distill under reduced pressure, stir at 122 °C for 100 min, cool to room temperature, add to the premix and stir evenly. Add sodium tripolyphosphate, stir at 62 °C for 18 min, add sodium chlorite, stir for 1.5 h, and cool to room temperature. Example 5

[0044] A high-efficiency liquid desulfurization and slag removal agent, whose raw materials include: 10kg of 150-mesh limestone powder, 0.5kg of sodium chlorate, 22kg of oleic acid, 2kg of sodium hydroxide, 0.5kg of yttrium chloride, 0.0998kg of sodium fluoride, 0.2153kg of sodium dichromate, 2kg of ethylenediamine, 3.5kg of methyl acrylate, 10kg of sodium tripolyphosphate, and 28kg of sodium chlorite.

[0045] The preparation method of the above-mentioned high-efficiency liquid desulfurization and deslagging agent comprises the following steps:

[0046] S1. Add 10 kg of 40% ethanol aqueous solution to oleic acid and stir evenly, add sodium hydroxide and stir evenly, add yttrium chloride thereto, stir at a speed of 800 r / min for 10 min, add 1.5 mol / L sodium fluoride aqueous solution thereto, continue stirring for 3 min, send into a hydrothermal reactor, treat at a temperature of 190°C for 8 h, add cyclohexane to precipitate after cooling, wash with ethanol to obtain activated rare earth;

[0047] S2, activated rare earth is added to 30kg water, and a sodium dichromate aqueous solution with a concentration of 0.05mol / L is added thereto under stirring, stirred for 20h at a speed of 800r / min, centrifuged, washed, vacuum dried, added to 45kg water and stirred evenly, limestone powder is added thereto and stirred for 90min, the stirring speed is 80r / min, sodium chlorate is added and stirred for 90min, and a premix is ​​obtained;

[0048] S3. Add ethylenediamine to 13 kg of methanol and stir evenly. Add methyl acrylate, stir at 45 °C for 15 h under nitrogen protection, heat to 75 °C and distill under reduced pressure, stir at 125 °C for 90 min, cool to room temperature, add to the premix and stir evenly, add sodium tripolyphosphate, stir at 65 °C for 15 min, add sodium chlorite, stir for 2 h, and cool to room temperature. Comparative Example 1

[0049] A high-efficiency liquid desulfurization and slag removal agent, whose raw materials include: 10kg of 150-mesh limestone powder, 0.5kg of sodium chlorate, 0.5kg of yttrium chloride, 2kg of ethylenediamine, 3.5kg of methyl acrylate, 10kg of sodium tripolyphosphate, and 28kg of sodium chlorite.

[0050] The preparation method of the above-mentioned high-efficiency liquid desulfurization and deslagging agent comprises the following steps:

[0051] S1, yttrium chloride is added to 45kg water and stirred evenly, limestone powder is added thereto and stirred for 90min at a stirring speed of 80r / min, sodium chlorate is added and stirred for 90min to obtain a premix;

[0052] S2. Add ethylenediamine to 13 kg of methanol and stir evenly. Add methyl acrylate, stir at 45 °C for 15 h under nitrogen protection, heat to 75 °C and distill under reduced pressure, stir at 125 °C for 90 min, cool to room temperature, add to the premix and stir evenly, add sodium tripolyphosphate, stir at 65 °C for 15 min, add sodium chlorite, stir for 2 h, and cool to room temperature. Comparative Example 2

[0053] A high-efficiency liquid desulfurization and slag removal agent, whose raw materials include: 10kg of 150-mesh limestone powder, 0.5kg of sodium chlorate, 22kg of oleic acid, 2kg of sodium hydroxide, 0.5kg of yttrium chloride, 0.0998kg of sodium fluoride, 2kg of ethylenediamine, 3.5kg of methyl acrylate, 10kg of sodium tripolyphosphate, and 28kg of sodium chlorite.

[0054] The preparation method of the above-mentioned high-efficiency liquid desulfurization and deslagging agent comprises the following steps:

[0055] S1. Add 10 kg of 40% ethanol aqueous solution to oleic acid and stir evenly, add sodium hydroxide and stir evenly, add yttrium chloride thereto, stir at a speed of 800 r / min for 10 min, add 1.5 mol / L sodium fluoride aqueous solution thereto, continue stirring for 3 min, send into a hydrothermal reactor, treat at a temperature of 190°C for 8 h, add cyclohexane to precipitate after cooling, wash with ethanol to obtain activated rare earth;

[0056] S2, adding activated rare earth to 45kg water and stirring evenly, adding limestone powder thereto and stirring for 90min, the stirring speed is 80r / min, adding sodium chlorate and stirring for 90min, to obtain a premix;

[0057] S3. Add ethylenediamine to 13 kg of methanol and stir evenly. Add methyl acrylate, stir at 45 °C for 15 h under nitrogen protection, heat to 75 °C and distill under reduced pressure, stir at 125 °C for 90 min, cool to room temperature, add to the premix and stir evenly, add sodium tripolyphosphate, stir at 65 °C for 15 min, add sodium chlorite, stir for 2 h, and cool to room temperature.

[0058] Desulfurization test was carried out using the desulfurization and deslagging agent obtained in Example 5 and Comparative Examples 1-2. Each group of samples was connected to a circulating pump and transported to a dosing box. The samples were blown into the tail of the boiler using compressed air from a vacuum tank. The flow rate of the metering pump was adjusted. The internal spraying meters should not be less than 2m, forming a spray state for uniform adsorption on the dust surface.

[0059] Taking Example 5 as an example, slaked lime powder was used for desulfurization from 6:10 to 8:50, the unit load was 32.2MW, the slaked lime powder dosage was 416.6kg / h, and the water dosage was 0.258t / h; then the desulfurization and deslagging agent obtained in Example 5 was used for desulfurization from 9:00 to 11:00, the average unit load was 32.4MW, the desulfurization and deslagging agent dosage was 120kg / h, and the water dosage was 0.12t / h. Specific monitoring data are shown in Table 1:

[0060] Table 1 Monitoring data of sulfur dioxide concentration and oxygen content after desulfurization of the unit from 6:10 to 11:00

[0061]

[0062] After the desulfurization test was carried out using the desulfurization and slag removal agents obtained in Example 5 and Comparative Examples 1-2, the monitoring data of sulfur dioxide concentration after desulfurization of each group were summarized, as shown in Table 2 (all units are mg / Nm³):

[0063] Table 2 Average, maximum and minimum sulfur dioxide concentrations after desulfurization for each unit from 6:00 to 11:00 per hour

[0064]

[0065] It can be seen from the above table that when each group of incinerators only used slaked lime for desulfurization treatment, the maximum instantaneous values ​​were similar (145mg / Nm³, 142mg / Nm³, 144mg / Nm³), and there was no significant difference; when the respective desulfurization and slag removal agents were used, the maximum instantaneous values ​​decreased by 19mg / Nm³, 15mg / Nm³, and 10mg / Nm³, respectively, proving that the desulfurization and slag removal agent obtained in Example 5 had the best effect, could effectively reduce the maximum instantaneous value, and significantly improved the desulfurization efficiency.

[0066] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A high-efficiency liquid desulfurization and slag removal agent, characterized in that: The raw materials include, by mass: 5-15 parts of limestone powder, 0.1-1 parts of catalyst, 20-25 parts of oleic acid, 1-3 parts of sodium hydroxide, 0.1-1 parts of yttrium chloride, 0.0403-0.1550 parts of sodium fluoride, 0.0131-0.3830 parts of sodium dichromate, 1-3 parts of ethylenediamine, 2-5 parts of methyl acrylate, 5-15 parts of sodium tripolyphosphate, and 20-35 parts of sodium chlorite; The preparation method of the high-efficiency liquid desulfurization and deslagging agent comprises the following steps: S1. Add ethanol aqueous solution to oleic acid and stir evenly, add sodium hydroxide and stir evenly, add yttrium chloride and stir for 5-15 minutes, add sodium fluoride aqueous solution and continue stirring for 1-5 minutes, perform hydrothermal treatment at 180-200° C. for 5-10 hours, add cyclohexane to precipitate after cooling, and wash to obtain activated rare earth; S2, adding activated rare earth to water, adding sodium dichromate aqueous solution thereto under stirring, continuing stirring for 10-30 hours, centrifuging, washing, vacuum drying, adding to water and stirring evenly, adding limestone powder thereto and stirring for 1-2 hours, adding a catalyst and stirring to obtain a premix; S3. Add ethylenediamine to methanol and stir evenly, add methyl acrylate, stir at 40-50°C for 10-20h under nitrogen protection, heat to 70-80°C and distill under reduced pressure, stir at 120-130°C for 1-2h, cool to room temperature, add to the premix and stir evenly, add sodium tripolyphosphate, stir at 60-70°C for 10-20min, add sodium chlorite, stir for 1-3h, and cool to room temperature.

2. The high-efficiency liquid desulfurization and slag removal agent according to claim 1, characterized in that: The catalyst is sodium chlorate.

3. The high-efficiency liquid desulfurization and slag removal agent according to claim 1, characterized in that: Limestone powder is obtained by crushing, grinding and sieving limestone.

4. The high-efficiency liquid desulfurization and slag removal agent according to claim 3, characterized in that: The sieve is 100-200 mesh.

5. A method for preparing a high-efficiency liquid desulfurization and deslagging agent as claimed in any one of claims 1 to 4, characterized in that: The steps include: S1. Add ethanol aqueous solution to oleic acid and stir evenly, add sodium hydroxide and stir evenly, add yttrium chloride and stir for 5-15 minutes, add sodium fluoride aqueous solution and continue stirring for 1-5 minutes, perform hydrothermal treatment at 180-200° C. for 5-10 hours, add cyclohexane to precipitate after cooling, and wash to obtain activated rare earth; S2, adding activated rare earth to water, adding sodium dichromate aqueous solution thereto under stirring, continuing stirring for 10-30 hours, centrifuging, washing, vacuum drying, adding to water and stirring evenly, adding limestone powder thereto and stirring for 1-2 hours, adding a catalyst and stirring to obtain a premix; S3. Add ethylenediamine to methanol and stir evenly, add methyl acrylate, stir at 40-50°C for 10-20h under nitrogen protection, heat to 70-80°C and distill under reduced pressure, stir at 120-130°C for 1-2h, cool to room temperature, add to the premix and stir evenly, add sodium tripolyphosphate, stir at 60-70°C for 10-20min, add sodium chlorite, stir for 1-3h, and cool to room temperature.

6. The method for preparing the high-efficiency liquid desulfurization and deslagging agent according to claim 5, characterized in that: In S1, the mass fraction of the ethanol aqueous solution is 30-50%.

7. The method for preparing the high-efficiency liquid desulfurization and deslagging agent according to claim 5, characterized in that: In S1, the concentration of the sodium fluoride aqueous solution is 1-2 mol / L.

8. The method for preparing the high-efficiency liquid desulfurization and deslagging agent according to claim 5, characterized in that: In S1, the hydrothermal treatment temperature is 185-195°C, and the hydrothermal treatment time is 7-9h.

9. The method for preparing the high-efficiency liquid desulfurization and deslagging agent according to claim 5, characterized in that: In S2, the concentration of the sodium dichromate aqueous solution is 0.01-0.1 mol / L.